Turmeric (Curcuma longa L.) and ginger (Zingiber officinale Rosc.) - world's invaluable medicinal spices : the agronomy and economy of turmeric and ginger /: the agronomy and economy of turmeric and ginger. ([2019]) - Nair, Kodoth Prabhakaran
No abstract available